Innovation @ ENEL : from monopoly power to open power - Chesbrough, Henry William, (SAGE Knowledge. Cases., 2017)
Enel is an innovative Italian energy utility that is undergoing rapid change. Technically the company has enthusiastically embraced renewable energy under its new CEO, Francesco Starace. The company is also shifting its business model away from the traditional cost plus regulatory model, towards a model built around a variety of value-add services. Open innovation is an important part of this transformation. There are internal barriers to overcome, and new organizational structures required, to manage this change.